Pemanfaatan Pelabelan Harmonis Graf Ular S_n Dalam Kriptografi Polialfabetik - Tahir, Fauzia D.; Katili, Muh Rifai; Yahya, Nisky Imansyah; Wungguli, Djihad; Asriadi; Nurwan; Armayani Arsal (Pendidikan Matematika Universitas PGRI Yogyakarta, 2025)
This research discusses harmonious labeling on the snake graph and its application in polyalphabetic cryptography. A harmonious labeling is an injective function from the set of vertices to the set of integers modulo , defined as . This function induces an edge labeling function . For each edge connecting vertices and , the edge label is given by , producing distinct edge labels. This study presents the construction process of harmonious labeling on the snake graph , where and . The results show that the snake graph satisfies the conditions for being harmoniously labeled since each edge receives a unique label. The vertex set of is defined as and the edge set as The harmonious labeling on this graph is then applied in cryptography, particularly in forming a cipher table used as a key in the polyalphabetic encryption and decryption process. This approach enhances cryptographic security, as a single plaintext letter can be transformed into various ciphertext possibilities, thereby increasing encryption strength and complicating message decryption attempts by unauthorized parties. Keywords: harmonious labeling, snake graph, cryptography, polyalphabetic cipher